2020
DOI: 10.3906/kim-2003-6
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence–based models for the qualitative and quantitative prediction of a phytochemical compound using HPLC method

Abstract: Isoquercitrin is a flavonoid chemical compound that can be extracted from different plant species such as Mangifera indica (mango), Rheum nobile, Annona squamosal, Camellia sinensis (tea), and coriander (Coriandrum sativum L.). It possesses various biological activities such as the prevention of thromboembolism and has anticancer, antiinflammatory, and antifatigue activities. Therefore, there is a critical need to elucidate and predict the qualitative and quantitative properties of this phytochemical compound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Our study results showed that out of 209 participant's shows 64.6% of participants had minimal to mild anxiety while 34.6% had moderate to severe anxiety in accordance with the generalized anxiety disorder -7 (GAD-7) scale. In comparison with another study from Spain results show that, regarding the initial psychological responses of the members of the University of Valladolid from March 28 to April4, 2020, two weeks after the lockdown of the Spaniard population due to the COVID-19 pandemic, 34.19% of participants reported moderate to extremely severe depression symptoms; 21.34% of participants re-ported moderate to extremely severe anxiety symptoms; and 28.14% reported moderate to extremely severe stress symptoms (18). One of the disadvantages of this study as most other studies is the lack of anxiety test results before lockdown which seems to be a critical factor as a study conducted in Italy with pre-lockdown available results showed indeed a significant correlation between the mental health of students and the pandemic and its lockdown effects by using completed self-report measures assessing worry (Penn State Worry Questionnaire, PSWQ), anxiety (Anxiety Sensitivity Index, ASI-3) but this study was as well limited due to the lack of sufficient participants as only Twenty-five students were able to participate since they had pre-lockdown available results (19).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Our study results showed that out of 209 participant's shows 64.6% of participants had minimal to mild anxiety while 34.6% had moderate to severe anxiety in accordance with the generalized anxiety disorder -7 (GAD-7) scale. In comparison with another study from Spain results show that, regarding the initial psychological responses of the members of the University of Valladolid from March 28 to April4, 2020, two weeks after the lockdown of the Spaniard population due to the COVID-19 pandemic, 34.19% of participants reported moderate to extremely severe depression symptoms; 21.34% of participants re-ported moderate to extremely severe anxiety symptoms; and 28.14% reported moderate to extremely severe stress symptoms (18). One of the disadvantages of this study as most other studies is the lack of anxiety test results before lockdown which seems to be a critical factor as a study conducted in Italy with pre-lockdown available results showed indeed a significant correlation between the mental health of students and the pandemic and its lockdown effects by using completed self-report measures assessing worry (Penn State Worry Questionnaire, PSWQ), anxiety (Anxiety Sensitivity Index, ASI-3) but this study was as well limited due to the lack of sufficient participants as only Twenty-five students were able to participate since they had pre-lockdown available results (19).…”
Section: Discussionmentioning
confidence: 58%
“…In this architecture, different neurons act as processing units, which are then linked together via customizable weights and biases. The input, hidden, and output layers of ANNs act as a single or multi-layered system [18]. The feed-forward network with backpropagation algorithms is used in this innovative study (FFNN-BP).…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of forecasting models is the most important element in determining their performance success [25]- [29]. As a result, the generally used error metrics are used to evaluate the outputs of prediction models as well as to compare them to one another.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…This method was recently employed in diverse areas of chemistry such as spectroscopy, chromatography, synthesis and spectrometry successfully. Generally, SVM is categorized into two; the Support Vector Regression (SVR), which composed of prediction analysis and the Support Vector Classifiers (SVC) that deals with classification issues [31]. SVR can be denoted using…”
Section: Support Vector Regression (Svr)mentioning
confidence: 99%